PENGARUH KEPERCAYAAN KONSUMEN, KUALITAS INFORMASI PRODUK, DAN KEMUDAHAN PENGGUNAAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK BUSANA MUSLIM MELALUI LINK SHOPEE AFFILIATE DI MEDIA SOSIAL PADA MAHASISWA UIN RADEN FATAH PALEMBANG - Saffanah Dwie Ramadhani; Rachmania; Safitri Asrol (LPPM Universitas Nias Raya, 2026)
The development of Shopee Affiliate on social media influences purchasing decisions, but there are still obstacles in consumer trust, product information quality, and ease of use. This study aims to analyze the influence of these three factors on purchasing decisions for Muslim fashion products among students of UIN Raden Fatah Palembang. This study uses a quantitative method with multiple linear regression analysis through SPSS 25. This study uses a quantitative method, with data processing carried out using the IBM SPSS Statistics version 25 program. Data were obtained by distributing questionnaires to 100 respondents selected using a purposive sampling technique. The research instrument has been tested for validity and reliability, as well as through the classical assumption test before conducting the t-test, F-test, and calculation of the coefficient of determination (R²). The results of the study indicate that consumer trust does not show any influence on purchasing decisions for Muslim fashion products, while the quality of product information and ease of use have a positive and significant effect on purchasing decisions for Muslim fashion products. Simultaneously, these three variables have a positive and significant effect, evidenced by the calculated F value of 32.737 > 2.699 and a significance of 0.000. The R² value of 0.490 indicates that 49% of the variation in purchasing decisions is explained by these three variables.